Analysis of Final Semester Students' Level of Academic Anxiety Disorder Regarding Thesis - Cahyadi, Anggih Tri; Sulistyaningtyas, Nunik (JUPE : Jurnal Pendidikan Mandala, 2025)
Academic anxiety is a psychological condition that can hinder students in completing their academic tasks.This study aims to determine the level of anxiety disorders experienced by final-year students in completing their thesis. The research method used is a descriptive method with a total sampling technique, involving 51 eighth-semester students at STKIP Taman Siswa. Data was collected through a questionnaire measuring three aspects of anxiety: physiological symptoms, emotional symptoms, and behavioral symptoms. The results show that most students experience academic anxiety with varying intensity levels. In terms of physiological symptoms, 49% of students experience moderate anxiety, 21.6% experience mild anxiety, and 17.6% experience severe anxiety. Emotional symptoms are most dominant in the moderate category (47%) and mild category (33.3%), with 17.6% of students experiencing severe anxiety. Meanwhile, in the behavioral aspect, the majority of students experience moderate anxiety (52.9%) and mild anxiety (43.1%), with only 3.9% experiencing severe anxiety. This study indicates that academic anxiety has a significant impact on the physical, emotional, and behavioral conditions of final year students.